2007
DOI: 10.1109/tit.2006.887060
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Spectra of Trapping Sets in Regular and Irregular LDPC Code Ensembles

Abstract: We address the problem of evaluating the asymptotic, normalized distributions of a class of combinatorial configurations in random, regular, binary low-density parity-check (LDPC) code ensembles. Among the configurations considered are trapping and stopping sets 1 ; these sets represent induced subgraphs in the Tanner graph of a code that, for certain classes of channels, exhibit a strong influence on the height and point of onset of the error-floor. The techniques used in the derivations are based on large de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
73
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 15 publications
2
73
1
Order By: Relevance
“…Trapping sets are defined in [32] and [33] as any lengthbit vector denoted by a pair ( , ), where is the Hamming weight of the bit vector and is the number of unsatisfied checks. An absorbing set could be understood as a special type of such trapping set where each variable node is connected to strictly more satisfied than unsatisfied checks.…”
Section: A Characterization Of Error Eventsmentioning
confidence: 99%
“…Trapping sets are defined in [32] and [33] as any lengthbit vector denoted by a pair ( , ), where is the Hamming weight of the bit vector and is the number of unsatisfied checks. An absorbing set could be understood as a special type of such trapping set where each variable node is connected to strictly more satisfied than unsatisfied checks.…”
Section: A Characterization Of Error Eventsmentioning
confidence: 99%
“…It was also observed that in the error-floor region, after running extensive Monte Carlo simulations, most of the error patterns correspond to the so-called elementary trapping sets [27], whose induced subgraphs have only degree-one and degree-two CNs. That is, for an elementary trapping set, the unsatisfied CNs are usually connected to the trapping set exactly once (there is one bit error per unsatisfied CN).…”
Section: Bi-mode Decodermentioning
confidence: 95%
“…They correspond to specific topological structures which characterize the behavior of the algorithm when it does not converge to a codeword. A fully absorbing set is a special type of trapping sets [24][32] [33], and is a fixed point of the Gallager B decoding algorithm [34]. For instance, if the all zero codeword is sent and the bits corresponding to the variables of the absorbing set are erroneous ('1' instead of '0'), the decoder will not be able to correct them and thus will not converge.…”
Section: Absorbing Setsmentioning
confidence: 99%